2013
DOI: 10.1007/s11748-013-0307-4
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous drain insertion in patients with post-operative extensive subcutaneous surgical emphysema: a single centre experience

Abstract: ESE should always be investigated and treated promptly. Early SCD insertion has a valuable role in the management of ESE with improvement of patients' experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…The finding might provide an important reference for the early identification of extensive subcutaneous emphysema after pulmonary resection by VATS in clinical practice. Kim et al and Boulemden et al also observed that extensive subcutaneous emphysema occurred within 1 and 3 days postoperatively [3,22], respectively, which was consistent with our results. However, there was a difference in the inclusion criteria between these two studies and the present study.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The finding might provide an important reference for the early identification of extensive subcutaneous emphysema after pulmonary resection by VATS in clinical practice. Kim et al and Boulemden et al also observed that extensive subcutaneous emphysema occurred within 1 and 3 days postoperatively [3,22], respectively, which was consistent with our results. However, there was a difference in the inclusion criteria between these two studies and the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In this present study, the incidence of extensive subcutaneous emphysema after pulmonary resection was 2.05% (89/4339), which is similar to the results of Boulemden et al [ 3 ]. In addition, about 75.58% (65/86) of the cases of extensive subcutaneous emphysema occurred within 1 to 4 days after surgery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Direct tear caused by the tube was rare. [7][8][9] Intraoperatively, he had normal peak pressures with no episode of desaturation and difficulty in ventilation excluding pneumothorax and above mentioned anesthesia causes. He had smooth induction and extubation excluding SE due to coughing against closed airway.…”
Section: Discussionmentioning
confidence: 95%